Building blocks of SOA Governance establishing demand and supply centers is a reliable approach for SOA governance. - Dayasindhu, N.
SOA initiatives have gathered momentum in the past year with more enterprises either implementing SOA or considering implementing in the near future. The implementations we studied reveal that one of the critical challenges in SOA is designing an effective governance mechanism. A good understanding of governance concepts is essential to implementing and operating a successful SOA. Reliable governance for SOA leads to a manifold increase in an enterprise's ability to achieve the goal of business agility through SOA.